Europeanized separatism: An European concept of independence movements - Roland Brandtjen (IU Internationale Hochschule, 2024)
There are some very well-known independence movements in Europe. However, most of these movements and parties are less well-known. In an increasingly integrated and harmonized Europe, the question arises as to how the parties and movements are influenced by the European level. The fact is that the largest political, social and economic actor in Europe, with which an emerging state must act, is the EU. However, little research has been done on this. The question arises as to whether possible full EU membership is an argument for regions to declare their own state. What does the population say about this? Are there any possible explanations for the answer? This paper attempts to explore and fill a scientific gap on this topic by presenting the results of adapted quantitative surveys conducted in 2019 and 2023 in all the mentioned regions. They are analysed by descriptive statistics. Correlation between regional language use and regional wealth, meaning of regional language use for the population and regional prosperity as well as the meaning of own unique culture for the regional population and the stated desired degree of autonomy are calculated and interpreted. The paper concludes with a Conclusion, the bibliography and an annex.
Keywords: 650; Europeanization; Separatism; Europeanized Separatism; quantitative research; Independence Movements